Correction: Loiko, N.; Islam, M.N. Plant–Soil Microbial Interaction: Differential Adaptations of Beneficial vs. Pathogenic Bacterial and Fungal Communities to Climate-Induced Drought. Agronomy 2024, 14, 1949 - Nataliya Loiko; M. Nazrul Islam (Agronomy)
In the publication [...]